Electrical production cost of young coconut waste pellet by using mini pellet mill-a feasibility study - Norain Idris; Intan Mastura Saadon; Aziean Mohd Azize; Muhammad Zulfattah bin Zakaria (Institute of Advanced Engineering and Science, 2020)
Biomass from plants, which have lignocellulosic structure have low bulk density of 30 kg/m3, is suitable to be pelletized to increase its specific density (gravity) for easy and inexpensive handling and storage. A new biomass waste material has evolved in interest due to abundant young coconut waste produced from famous young coconut drink and shake business in Melaka, Malaysia. The young coconut pelletization feasibility needs to be verified by firstly assessing its electrical production cost. Therefore, this paper aims to measure the electrical production cost for process involved in young coconut pelletization and analyze its competitiveness against other biomass material from other countries. This is executed by assessing the electrical production cost of three main process in pelletization; crushing, drying and pelleting. The equipments used are coconut crusher, lab-scaled industrial oven and mini pellet mill. The result demonstrates a significantly high electrical production cost, which is MYR141,430/tonne, while other material’s production cost only amounts to couple of Malaysian hundreds. Processes’ efficiency need to be massively improved by using drum drying method and by adding blender after crusher to increase the desired grain size to avoid raw material wastage. Electrical tariff must also be switched from commercial to industrial tariff.